2014
DOI: 10.1155/2014/752182
|View full text |Cite
|
Sign up to set email alerts
|

How to Motivate Whole Blood Donors to Become Plasma Donors

Abstract: This study tested the efficacy of interventions to recruit new plasma donors among whole blood donors. A sample of 924 donors was randomized to one of three conditions: control; information only by nurse; and information plus self-positive image message by nurse (SPI). Participants in the control condition only received a leaflet describing the plasma donation procedure. In the two experimental conditions the leaflet was explained face-to-face by a nurse. The dependent variables were the proportion of new plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 10 publications
1
23
0
1
Order By: Relevance
“…This result underscores the unique nature of plasma/platelet donation, which is far more demanding than whole-blood donation. When behaviors are demanding, individuals must truly believe that there is a benefit to this behavior in order to take action [47,57]. In short, donors who engage in this type of donation practice seem driven more by benevolence than by altruism [58].…”
Section: Different Motivations According To Donor Typementioning
confidence: 99%
“…This result underscores the unique nature of plasma/platelet donation, which is far more demanding than whole-blood donation. When behaviors are demanding, individuals must truly believe that there is a benefit to this behavior in order to take action [47,57]. In short, donors who engage in this type of donation practice seem driven more by benevolence than by altruism [58].…”
Section: Different Motivations According To Donor Typementioning
confidence: 99%
“…The particular importance of indirect reciprocity for PPDs (“it gives me a sense of pride,” “I like to have goals”) also underscores the unique nature of a blood donation practice that is far more demanding than whole blood donation. When the personal cost is high, beliefs in personal benefits are more important for promoting actions [ 15 , 44 ]. In short, donors who engage in this type of donation practice seem driven more by benevolence than by altruism [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological research suggests that different determinants have been associated with the intention to convert to apheresis: age, frequency of WB donations, feeling good and being proud, a sense of obligation, perceived social pressure, ease, and confidence . Personalized communications from the BCA were also positively associated with intention to convert . Critical belief analysis revealed that the family's influence was vital to conversion, but support of colleagues was more important to the continuation of plasmapheresis .…”
Section: Introductionmentioning
confidence: 98%
“…The majority of research on apheresis donation has focused on donors' socio‐economic profiles, conversion process, barriers (deterrents), and donors' motivations . Some of these studies were conducted in countries where remuneration for plasmapheresis or plateletpheresis is available .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation